Sistem Informasi Helpdesk Berbasis Web Menggunakan Metode Prototype Pada PT. Denso Manufacturing Indonesia - Elkin Rilvani (Jurnal SIGMA, 2020)
In manufacturing companies, currently, information systems are needed to support all activities within the company to smoothen the business process, in order to work IT users still use paper media to carry out work orders so that problems with users are not handled quickly by the IT team. The existence of a Helpdesk information system at PT Denso Manufacturing Indonesia to assist users in requesting problems that occur in hardware, software and networks on their computers so that problems can be resolved quickly by the IT team and this Helpdesk information system also helps the IT team in solving problems that often occur can be minimized with solutions that have been experienced before. The method used in the helpdesk information system at PT Denso Manufacturing Indonesia is using the prototype method where this method is very helpful for the IT team in developing a Helpdesk information system. The results of this study are the implementation of the helpdesk information system so that it can be used by all employees at PT Denso Manufacturing Indonesia who use computers to do work so that they are easy to request problems that occur on their computers. With this Helpdesk information system, all problems can be seen directly through this system, do not have to be calculated manually and can help the work of the head of the IT sector in making decisions, from the exported data it can describe problems related to network connections, software damage, hardware damage so that it can see the extent of the problems handled by the Helpdesk Support team at PT Denso Manufacturing Indonesia. Keywords: Helpdesk System, Web, Denso Helpdesk